Revisiting Frank–Starling: regulatory light chain phosphorylation alters the rate of force redevelopment (ktr) in a length‐dependent fashion. (24th July 2016) - Toepfer, Christopher N.; West, Timothy G.; Ferenczi, Michael A.
Abstract : Key points: Regulatory light chain (RLC) phosphorylation has been shown to alter the ability of muscle to produce force and power during shortening and to alter the rate of force redevelopment ( k tr ) at submaximal [Ca 2+ ]. Increasing RLC phosphorylation ∼50% from the in vivo level in maximally [Ca 2+ ]‐activated cardiac trabecula accelerates k tr . Decreasing RLC phosphorylation to ∼70% of the in vivo control level slows k tr and reduces force generation. k tr is dependent on sarcomere length in the physiological range 1.85–1.94 μm and RLC phosphorylation modulates this response. We demonstrate that Frank–Starling is evident at maximal [Ca 2+ ] activation and therefore does not necessarily require length‐dependent change in [Ca 2+ ]‐sensitivity of thin filament activation. The stretch response is modulated by changes in RLC phosphorylation, pinpointing RLC phosphorylation as a modulator of the Frank–Starling law in the heart. These data provide an explanation for slowed systolic function in the intact heart in response to RLC phosphorylation reduction. Abstract: Force and power in cardiac muscle have a known dependence on phosphorylation of the myosin‐associated regulatory light chain (RLC). We explore the effect of RLC phosphorylation on the ability of cardiac preparations to redevelop force ( k tr ) in maximally activating [Ca 2+ ]. Activation was achieved by rapidly increasing the temperature (temperature‐jump of 0.5–20ºC) of permeabilized trabeculae over a physiological range of sarcomere lengths (1.85–1.94 μm). The trabeculae were subjected to shortening ramps over a range of velocities and the extent of RLC phosphorylation was varied. The latter was achieved using an RLC‐exchange technique, which avoids changes in the phosphorylation level of other proteins. The results show that increasing RLC phosphorylation by 50% accelerates k tr by ∼50%, irrespective of the sarcomere length, whereas decreasing phosphorylation by 30% slows k tr by ∼50%, relative to the k tr obtained for in vivo phosphorylation. Clearly, phosphorylation affects the magnitude of k tr following step shortening or ramp shortening. Using a two‐state model, we explore the effect of RLC phosphorylation on the kinetics of force development, which proposes that phosphorylation affects the kinetics of both attachment and detachment of cross‐bridges. In summary, RLC phosphorylation affects the rate and extent of force redevelopment. These findings were obtained in maximally activated muscle at saturating [Ca 2+ ] and are not explained by changes in the Ca 2+ ‐sensitivity of acto‐myosin interactions. The length‐dependence of the rate of force redevelopment, together with the modulation by the state of RLC phosphorylation, suggests that these effects play a role in the Frank–Starling law of the heart. Key points: Regulatory light chain (RLC) phosphorylation has been shown to alter the ability of muscle to produce force and power during shortening and to alter the rate of force redevelopment ( k tr ) at submaximal [Ca 2+ ]. Increasing RLC phosphorylation ∼50% from the in vivo level in maximally [Ca 2+ ]‐activated cardiac trabecula accelerates k tr . Decreasing RLC phosphorylation to ∼70% of the in vivo control level slows k tr and reduces force generation. k tr is dependent on sarcomere length in the physiological range 1.85–1.94 μm and RLC phosphorylation modulates this response. We demonstrate that Frank–Starling is evident at maximal [Ca 2+ ] activation and therefore does not necessarily require length‐dependent change in [Ca 2+ ]‐sensitivity of thin filament activation. The stretch response is modulated by changes in RLC phosphorylation, pinpointing RLC phosphorylation as a modulator of the Frank–Starling law in the heart. These data provide an explanation for slowed systolic function in the intact heart in response to RLC phosphorylation reduction.